Unilever Platinum Stores: Building a brand for the community - ZERRILLO, Philip C. (Institutional Knowledge at Singapore Management University, 2015)
This case describes the conception and development of an innovative store concept by Unilever, Thailand, and illustrates the challenges of setting up and scaling a corporate social responsibility (CSR) project that involves the active participation of the members of the community. Against the backdrop of Thailand’s worst floods in over 60 years, Ratchtar Karasuddhi (‘Jack’), the head of business development for general trade at Unilever, comes up with an idea of assisting a flood stricken owner of a mom and pop shop (a local neighbourhood convenience store). Looking at the location of the shop, Jack believed that with some upgrading and better visibility, the shop could not only be revived, but become a serious alternative to the nearby modern trade convenience store. What started out as a simple wish to help a single distressed shop owner, soon spawned into a viable business idea that would benefit the local community and the company. The number of Star Stores, or Platinum Stores as they were called within Unilever, expanded rapidly – the first outlet was inaugurated in March 2012 and there were 7,800 Platinum Stores by July 2014. The frenetic growth in the number of stores eventually showed strain on the execution side of the business, as the operations side struggled to cope with the fact that four to five new outlets were being opened each day. Each store required the full engagement with and cooperation of the shop owner, a customised planogram, and training and capability building of the shop owner. Looking ahead, what will determine the sustained success of Platinum Stores in Thailand?